Anthropogenic disturbance reduces seed-dispersal services for myrmecochorous plants in the Brazilian Caatinga - Leal, Laura C.; Andersen, Alan N.; Leal, Inara R. (Oecologia, 2014)
Anthropogenic disturbance can have important indirect effects on ecosystems by disrupting species interactions. Here we examine the effects of anthropogenic disturbance on distance dispersal by ants for the diaspores of myrmecochorous Euphorbiaceae in Brazilian Caatinga. Rates of diaspore removal and distances removed of Croton sonderianus and Jatropha mollissima were observed at 24 sites ranging from low to very high disturbance (primarily grazing by livestock, hunting and firewood collection). Despite a large number of seed-disperser ant species, there were only two species providing high-quality distance-dispersal services, Dinoponera quadriceps (40 % of all observed seed removals) and Ectatomma muticum (33 %). D. quadriceps was responsible for 97 % of all removals >2 m, and 100 % of all removals >5 m. Removal rates did not vary with disturbance for C. sonderianus (small elaiosome), but declined with increasing disturbance for J. mollissima (large elaiosome). The number of removals by Ectatomma was highest at intermediate levels of disturbance, whereas those by Dinoponera decreased systematically with increasing levels of disturbance. Mean dispersal distance was four times higher at sites experiencing low disturbance, where removals >5 m represented a third of all removal events, compared with very highly disturbed sites, where no removals >5 m were observed. Despite high overall diversity there is very limited functional redundancy in disperser ant species, resulting in low disperser resilience in relation to disturbance. This is likely to have important implications for recruitment by myrmecochorous plants, and therefore on vegetation composition and structure, at sites subject to high anthropogenic disturbance.